Formative mixed-method multicase study research to inform the development of a safer sex and healthy relationships intervention in further education (FE) settings: the SaFE Project. Issue 7 (9th July 2019) - Young, Honor; Turney, Catherine; White, James; Lewis, Ruth; Bonell, Christopher
Abstract : Objectives: Sexual health includes pleasurable, safe, sexual experiences free from coercion, discrimination and violence. In the UK, many young people's experiences fall short of this definition. This study aimed to inform the development of a safer sex and healthy relationships intervention for those aged 16–19 years studying in further education (FE) settings. Design: A formative mixed-method multicase study explored if and how to implement four components within a single intervention. Setting: Six FE settings in England and Wales and one sexual health charity participated between October and July 2015. Participants: Focus groups with 134 FE students and 44 FE staff, and interviews with 11 FE managers and 12 sexual health charity staff, first explored whether four candidate intervention components were acceptable and could have sustained implementation. An e-survey with 2105 students and 163 staff then examined potential uptake and acceptability of components shortlisted in the first stage. Stakeholder consultation was then used to refine the intervention. Intervention: Informed by a review of evidence of effective interventions delivered in other settings, four candidate intervention components were identified which could promote safer sex and healthy relationships among those aged 16–19 years: 1) student-led sexual health action groups; 2) on-site sexual health and relationships services; 3) staff safeguarding training about sexual health and relationships and 4) sex and relationships education. Results: On-site sexual health and relationships services and staff safeguarding training about sexual health and relationships were key gaps in current FE provision and welcomed by staff, students and health professionals. Sex and relationships education and student-led sexual health action groups were not considered acceptable. Conclusions: The SaFE intervention, comprising on-site sexual health and relationships services and staff safeguarding training in FE settings, may have potential promoting sexual health among FE students. Further optimisation and refinement with key stakeholders is required before piloting via cluster randomised controlled trial.